2018
DOI: 10.1177/2058460118808811
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast-enhanced magnetic resonance imaging may act as a biomarker for vascular damage in normal appearing brain tissue after radiotherapy in patients with glioblastoma

Abstract: BackgroundDynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) is a promising perfusion method and may be useful in evaluating radiation-induced changes in normal-appearing brain tissue.PurposeTo assess whether radiotherapy induces changes in vascular permeability (Ktrans) and the fractional volume of the extravascular extracellular space (Ve) derived from DCE-MRI in normal-appearing brain tissue and possible relationships to radiation dose given.Material and MethodsSeventeen patients with glioblasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…(62 ± 9) HGG III–IV CBF↑ 0–18% after 2-4 m vs T0 Weber [ 42 ] 1.5T 25/11F (25–73) Metastases SRS 16-20 Gy PASL ↔ CBF WM/GM until 6 m vs T0 Artzi [ 50 ] 3T 26/16 (51 ± 12) HGG III–IV RTx, BEV DCE ↔ V p in WM or GM vs T0 11/? (37 ± 11) HC No Cao [ 47 ] 1.5T 10/1F (45 ± 16) CNS I–III 3D-CRTx 50-60 Gy DCE V p ↑ 12% after 1 m, K trans ↑ 52% at w6 of therapy vs T0 Fahlström [ 48 ] 1.5T 12/?F (56 ± 11) HGG III–IV IMRTx 60 Gy, TMZ 75 mg/m2, BEV DCE V e ↑ 8% after 3 m vs T0 Farjam [ 49 ] 1.5T 27/10F (50 ± 12) CNS I–III IMRT/3DCRTx 50-60 Gy DCE K trans ↑ in hippocampus after 1 m vs T0 Wong [ 51 ] 3T 14/9F (?) Metastases WBRTx 37.5 Gy DCE ↔ after 1–5 months vs T0 Gulaldi [ 33 ] SPECT 18/5F (42 ± 13) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(62 ± 9) HGG III–IV CBF↑ 0–18% after 2-4 m vs T0 Weber [ 42 ] 1.5T 25/11F (25–73) Metastases SRS 16-20 Gy PASL ↔ CBF WM/GM until 6 m vs T0 Artzi [ 50 ] 3T 26/16 (51 ± 12) HGG III–IV RTx, BEV DCE ↔ V p in WM or GM vs T0 11/? (37 ± 11) HC No Cao [ 47 ] 1.5T 10/1F (45 ± 16) CNS I–III 3D-CRTx 50-60 Gy DCE V p ↑ 12% after 1 m, K trans ↑ 52% at w6 of therapy vs T0 Fahlström [ 48 ] 1.5T 12/?F (56 ± 11) HGG III–IV IMRTx 60 Gy, TMZ 75 mg/m2, BEV DCE V e ↑ 8% after 3 m vs T0 Farjam [ 49 ] 1.5T 27/10F (50 ± 12) CNS I–III IMRT/3DCRTx 50-60 Gy DCE K trans ↑ in hippocampus after 1 m vs T0 Wong [ 51 ] 3T 14/9F (?) Metastases WBRTx 37.5 Gy DCE ↔ after 1–5 months vs T0 Gulaldi [ 33 ] SPECT 18/5F (42 ± 13) …”
Section: Resultsmentioning
confidence: 99%
“…No other DCE studies gave clear results. Transient V e increase by 8% was observed in GM 3 months post-RTx, but K trans and V e at other times had similar magnitudes but were not significant [ 48 ]. A longitudinal K trans increase in the hippocampus was claimed one month after RTx, without providing details of the effect size [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Radiation-induced vascular changes can be detected with perfusion-weighted imaging (PWI) methods such as dynamic susceptibility contrast (DSC), dynamic contrast enhancement (DCE), and arterial spin labeling (ASL). Most PWI studies found a perfusion decrease after radiotherapy, characterized by decreasing cerebral blood volume (CBV) [ 84 , 97 , 98 , 99 , 100 ], decreasing cerebral blood flow (CBF) [ 36 , 84 , 95 , 98 , 101 ], and increased K trans (volume transfer constant between blood plasma and extravascular extracellular space (EES)), v e (volume of EES) and v p (fractional plasma volume) [ 102 , 103 ]. Table 3 summarizes the results of the studies focusing on vascular changes of normal-appearing brains after irradiation.…”
Section: Determination Of Vascular Changes In Normal-appearing Tismentioning
confidence: 99%
“…Using DCE, Fahlström et al [ 102 ] analyzed K trans and v e in WM and GM after irradiation in 17 glioblastoma patients over a period of up to 185.7 days. While global K trans in WM and GM did not change significantly, v e showed a significant increase in GM 101.6 days after RT.…”
Section: Determination Of Vascular Changes In Normal-appearing Tismentioning
confidence: 99%
“…In fact, DCE-MRI data analysis is affected by (a) the acquisition protocol (trade-off between spatial and temporal resolution) [17] and (b) the quantification procedure. Furthermore, most studies present only results from application of a single pharmacokinetic model and the consequent statistical analysis of averaged values evaluated over the whole tumour volume [1820]. This approach completely ignores the particularly heterogeneous nature of brain tumour vasculature and vascular permeability.…”
Section: Introductionmentioning
confidence: 99%